2010
DOI: 10.4103/0974-7788.72488
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperglycemic activity of Tectona grandis Linn. bark extract on alloxan induced diabetes in rats

Abstract: Tectona Grandis Linn.(saag - tick wood), an indigenous medicinal plant, has a folk reputation among the Indian herbs as a hypoglycemic agent. The present study was carried out to evaluate the anti-hyperglycemic effect of T. grandis Linn. bark extract in control and alloxan-diabetic rats. Oral administration of the bark suspension of T. grandis (2.5 and 5 g/kg body wt.) for 30 days resulted in a significant reduction in blood glucose (from 250 ± 6.5 to 50 ± 2.5 mg/dL). Thus, the present study clearly shows that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…Previous phytochemical research reported that T. grandis was not only rich in flavonoids and quinones, but also contained phenolic, steroids, phenylpropanoids, fatty esters and other compounds [ 2 ]. In ethnomedicine, T. grandis is commonly used to treat wounds, pain, fever, malaria, inflammation, diabetes, liver disease, helminthic infection, bronchitis, tumors, cholelithiasis, jaundice, skin disease and bacterial infection [ 3 , 4 , 5 , 6 , 7 ]. Pharmacological studies conducted on the methanolic extracts of T. grandis bark and flowers established its hypoglycemic activities [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous phytochemical research reported that T. grandis was not only rich in flavonoids and quinones, but also contained phenolic, steroids, phenylpropanoids, fatty esters and other compounds [ 2 ]. In ethnomedicine, T. grandis is commonly used to treat wounds, pain, fever, malaria, inflammation, diabetes, liver disease, helminthic infection, bronchitis, tumors, cholelithiasis, jaundice, skin disease and bacterial infection [ 3 , 4 , 5 , 6 , 7 ]. Pharmacological studies conducted on the methanolic extracts of T. grandis bark and flowers established its hypoglycemic activities [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that effective control of the blood glucose level is a key step in preventing or reversing diabetic complications and improving the quality of life in diabetic patients [ 38 , 39 , 40 ]. The hypoglycemic activity of salidroside in alloxan-induced diabetic mice has been indicated here by estimation of fasting blood glucose levels, as the important basal parameter for monitoring of diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…The anti-hyperglycemic activity of Tectona grandis bark extract may be due to the regeneration of islets' β-cells following destruction by alloxan, as the extract shows significant reduction of blood glucose levels in 15 and 30 days, at a dosage of 2.5 and 5 g/kg body wt. 61 In a study, ethenolic extract of bark of Tectona grandis showed significant decrease in plasma glucose and serum triglyceride levels at the dose of 100 and 200 mg/kg, p.o. and also stimulated glucose uptake in skeletal muscles.…”
Section: Tectona Grandis Linnmentioning
confidence: 99%